Trade and the political economy of redistribution - Gonzague Vannoorenberghe; Eckhard Janeba (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper analyzes the effects of trade liberalisation on the political support for policies that redistribute income between workers in different sectors. We allow for worker heterogeneity and imperfect mobility of workers across sectors, giving rise to a trade-off between redistribution and the inefficiency of the labor allocation. We compare two environments, autarky and small open economy, and present three main findings. First, redistributive policies are more likely to arise in a small open than in a closed economy. Second, if a redistributive policy is adopted in both situations, its nominal level is higher in autarky than in the small open economy. Third, even though voters choose redistributive policies with lower nominal value in open economies, the actual extent of redistribution in equilibrium is larger in the open than in the closed economy. We discuss our results in the context of the debate about the effects of globalisation on government activity.
Keywords: F10; H20; 330; international trade; redistribution; political economy; factor mobility; Außenhandelsliberalisierung; Einkommensumverteilung; Public Choice; Mehr-Sektoren-Modell; Arbeitsmobilität; Kleines-offenes-Land; Theorie